An efficient regrouping method of retired lithium-ion iron phosphate batteries based on incremental capacity curve feature extraction for echelon utilization. (1st December 2022) - Chen, Zuhang; Deng, Yelin; Li, Honglei; Liu, Weiwei
Abstract: Due to the long service life of lithium-ion iron phosphate (LFP) batteries, retired LFP batteries from electric vehicles are suitable for echelon utilization. Sorting and regrouping should be carried out in advance to ensure the performance of retired LFP batteries. Effective methods are often time consuming and expensive. The incremental capacity (IC) curve, derived from the capacity-voltage curve, is often employed to analyze the aging mechanism of batteries. Compared with the existing methods, it is relatively economical and can reflect the batteries' long-term consistency of the capacity loss. Therefore, a sorting and regrouping method based on the IC curve is proposed and applied to 320 retired LFP batteries. The peaks of the IC curve were extracted as the features and used for sorting. In the regrouping, the K-means++ algorithm was applied for clustering, and then the t- test was used to further improve the regrouping consistency. The mean squared error (MSE) of each group generally decreased by more than 60 % from the previously 0.04 MSE level. Finally, the validation experiment showed that short-term consistency was improved by more than 5 times compared with randomly grouped batteries, and the capacity gap of the same groups of batteries was less than 3 times that of the different groups. Highlights: Both short-term and long-term consistencies of batteries' performances are simultaneously evaluated for regrouping. Incremental Capacity (IC) curve is directly used for regrouping of retired batteries. The combination of K-means algorithm and t -test provides an excellent regrouping effect.